Direct amplitude detuning measurement with ac dipole - S. White; E. Maclean; R. Tomás (Physical Review Special Topics. Accelerators and Beams, 2013)
In circular machines, nonlinear dynamics can impact parameters such as beam lifetime and could result in limitations on the performance reach of the accelerator. Assessing and understanding these effects in experiments is essential to confirm the accuracy of the magnetic model and improve the machine performance. A direct measurement of the machine nonlinearities can be obtained by characterizing the dependency of the tune as a function of the amplitude of oscillations (usually defined as amplitude detuning). The conventional technique is to excite the beam to large amplitudes with a single kick and derive the tune from turn-by-turn data acquired with beam position monitors. Although this provides a very precise tune measurement it has the significant disadvantage of being destructive. An alternative, nondestructive way of exciting large amplitude oscillations is to use an ac dipole. The perturbation Hamiltonian in the presence of an ac dipole excitation shows a distinct behavior compared to the free oscillations which should be correctly taken into account in the interpretation of experimental data. The use of an ac dipole for direct amplitude detuning measurement requires careful data processing allowing one to observe the natural tune of the machine; the feasibility of such a measurement is demonstrated using experimental data from the Large Hadron Collider. An experimental proof of the theoretical derivations based on measurements performed at injection energy is provided as well as an application of this technique at top energy using a large number of excitations on the same beam.